1997
DOI: 10.1007/bf00175264
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of uveitis in a referral uveitis clinic in India

Abstract: This report describes a retrospective study of all new patients in our uveitis clinic between January 1992 and December 1994, undertaken to identify the pattern of uveitis in the Indian subcontinent. A standard clinical protocol, and the naming-meshing system with tailored laboratory investigations were used to arrive at a final uveitic diagnosis. Uveitis comprised 1.5% of new cases seen at the centre. Out of 1273 uveitis cases, anterior uveitis was the most common type (39.28%), followed by posterior uveitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
111
6
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 12 publications
17
111
6
5
Order By: Relevance
“…However, the mean age at presentation in our study (34 years) appeared to be younger than that found in most previous reports (approximately 40 years). 9,12,14,15 The rate of children in our uveitis population (10%) was slightly higher than most estimates from previous studies. [30][31][32] Data from referral centres revealed that anterior uveitis was the most common form of uveitis (27.8-63%), followed by posterior (9.3-38%) or panuveitis (7-38%), and intermediate uveitis (4-17%).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, the mean age at presentation in our study (34 years) appeared to be younger than that found in most previous reports (approximately 40 years). 9,12,14,15 The rate of children in our uveitis population (10%) was slightly higher than most estimates from previous studies. [30][31][32] Data from referral centres revealed that anterior uveitis was the most common form of uveitis (27.8-63%), followed by posterior (9.3-38%) or panuveitis (7-38%), and intermediate uveitis (4-17%).…”
Section: Discussioncontrasting
confidence: 62%
“…14,15 However, these two declined infectious diseases are now re-emerging worldwide, particularly because of an increase in the human immunodeficiency virus-infected population. 15 Five patients in our study (1.1%) had posterior uveitis attributed to Mediterranean spotted fever, an infectious disease endemic in Mediterranean countries that is caused by R. conorii infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were classified according to the current International Uveitis Study Group (IUSG); classification based on the localization of intraocular inflammation. 1 Ancillary tests included B scan ultrasound, fundus fluorescein angiography in selected cases and tailored laboratory investigations in each case. Standard diagnostic criteria were employed for all syndromes or entities of uveitis.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from our study is consistent with those from previous reports. 1,[19][20][21] This shows that majority of patients are students and of working age and so the condition may cause potentially serious economic consequences with many days off work as well as interfere with education.…”
Section: 14-18mentioning
confidence: 99%